2023
DOI: 10.1039/d2nr05810c
|View full text |Cite
|
Sign up to set email alerts
|

Growth pathways of exotic Cu@Au core@shell structures: the key role of misfit strain

Abstract: The CuAu system is characterized by a large lattice mismatch which causes a misfit strain in its core@shell architectures. Here we simulate the formation of Cu@Au core@shell nanoparticles by Au...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…39,40 This potential for AuCu, whose form and parameters are given in ref. 18 and 36, has been previously tested against DFT calculations 36 obtaining a good agreement.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 This potential for AuCu, whose form and parameters are given in ref. 18 and 36, has been previously tested against DFT calculations 36 obtaining a good agreement.…”
Section: Computational Detailsmentioning
confidence: 99%
“…10 In fact, AuCu nanoparticles with different chemical ordering arrangements have been obtained in several experiments and simulations. 11–18…”
Section: Introductionmentioning
confidence: 99%
“…39 Moreover, the development of faulted layers during crystal growth can be induced by a second metal in nanoalloys, 40−42 inducing surface reconstruction and decreasing the free surface energy to stabilize uncommon structures. 18,35,43,44 In this way, bimetallic systems present unusual MTP structures shaped from structural defects and composition inhomogeneities, which has repercussions in the free surface energy minimization in the small size regime.…”
mentioning
confidence: 99%
“…Recent studies demonstrated that the growth pathways for Dh and Ih formation depend on how initial tetrahedra form and evolve. These initial tetrahedra can stabilize new twin boundaries (TB) overgrowing into Dh or, subsequently, Ih . Moreover, the development of faulted layers during crystal growth can be induced by a second metal in nanoalloys, inducing surface reconstruction and decreasing the free surface energy to stabilize uncommon structures. ,,, In this way, bimetallic systems present unusual MTP structures shaped from structural defects and composition inhomogeneities, which has repercussions in the free surface energy minimization in the small size regime.…”
mentioning
confidence: 99%
See 1 more Smart Citation